ASM Handbook. Volume 14B, (ASM International, 2006)
Volume 14B on sheet forming is the second of two volumes on metalworking technology. This volume addresses all methods of sheet metal fabrication technologies, selection of equipment and die materials, specification of forming practices for specific alloys, and new techniques for process design and control. It provides practical reference information on the basic processes of press forming, drawing, bending, spinning, shearing, blanking, and piercing of sheet with additional coverage on forming with bar, tube, wire, shapes, or long parts -- publisher.